2015
DOI: 10.1016/j.matdes.2015.09.089
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ti-coating layer on the distribution of SiCP in the SiCP/2014Al composites

Abstract: a b s t r a c t A Ti 5 Si 3 coating layer was plated on the surface of SiC P by salt-bath plating. The coating layer greatly promoted the wettability of SiC by the molten Al with the final contact angle decreasing from 94°of uncoated one to 4°at 973 K. The 2 vol.% Ti-coated SiC P /2014Al composites were fabricated by stir casting with the addition of 20 vol.% Ti-coated SiC P /2014Al master alloy. Due to the significant improvement of the wetting between the Ti-coated SiC and Al melt, the interfacial energy bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Original SiC particles have a high wetting angle of 155° with respect to the aluminum matrix, indicating poor wettability at the interface. The weak interfacial bonding between the neat SiC particles and the aluminum matrix cannot efficiently transfer the external load from the aluminum matrix to the SiC particles to achieve reinforcement . Copper coating on the surface of SiC particles improves the interfacial bonding between SiC particles and the aluminum matrix, leading to a strengthening of the interface.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Original SiC particles have a high wetting angle of 155° with respect to the aluminum matrix, indicating poor wettability at the interface. The weak interfacial bonding between the neat SiC particles and the aluminum matrix cannot efficiently transfer the external load from the aluminum matrix to the SiC particles to achieve reinforcement . Copper coating on the surface of SiC particles improves the interfacial bonding between SiC particles and the aluminum matrix, leading to a strengthening of the interface.…”
Section: Resultsmentioning
confidence: 99%
“…Surface modification of SiC particles is an effective approach to improve the relative density and interfacial wettability. Several surface treatment techniques, such as the high‐temperature oxidation of SiC particles, and coating a layer of a suitable metal such as Cu, Ti, or Ni on the SiC particles have been adopted by researchers . However, the benefit of high‐temperature oxidation is adversely affected by the agglomeration of SiC particles at high temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Given the low wettability of ceramic particles [96,97], metallic coatings or oxidation of the interface is often performed before the reinforcement is introduced in the melt to improve reinforcement-matrix bonding. Among the available options, nickel and copper are the most common choices for electroless deposition coating [72,[98][99][100][101] [73]. It was reported that the formation of a Ti 5 Si 3 in the SiC/Ti interface would decrease its contact angle in a shorter period for 800 • C, leading to higher interfacial energy when compared with the uncoated samples.…”
Section: Discussionmentioning
confidence: 99%
“…Recommendations[10,68,71,73,[75][76][77]79,[81][82][83]91,94,95,163]. If not present in pre-processing; b no specific effect on MMC as it improves general casting quality.…”
mentioning
confidence: 99%
“…The conventional reinforcement, such as SiC [36][37][38], Ti(Al 3 Ti) [39], TiB 2 [40], Al 2 O 3 [41], are added in large quantities, which easily damage the elongation of composites due to agglomeration or poor interfacial bonding. Surface modification [42][43][44][45] can effectively improve the wettability and interfacial bonding, thus enhancing the strength and elongation. On the basis of surface modification, compared with the aforementioned conventional reinforcement, in situ Cu-NPs@GNPs synthesized in this work still shows much better comprehensive strengthening efficiency: the introduction of a small amount of graphene can achieve a good performance improvement, which accords with the development trend of composites as "light weight and high strength".…”
Section: Strengthening Mechanismsmentioning
confidence: 99%